Twice-exceptional students: a systematic review to outline the distinctive characteristics through a multidimensional lens - Rizzo, Ludovica; Pinnelli, Stefania; Minnaert, Alexander (Frontiers in Education, 2025)
IntroductionTwice-exceptionality can be described as a complex interaction between giftedness and one or more co-occurring challenges. Existing literature indicates that this coexistence may result in the inhibition of some characteristics typically associated with each condition when considered in isolation, the exacerbation of others, or the identification of new traits. However, limited data are available on this complex interplay, due to the small number of empirical studies conducted in this field, the difficulty in recruiting large samples, and the heterogeneous nature of the profiles investigated. This systematic review aims to identify the distinguishing characteristics of twice-exceptionality emerging from empirical studies conducted between January 2013 and January 2025.MethodsQualitative, quantitative, and mixed-methods studies were included and analyzed within a convergent integrated framework. Data were coded using MAXQDA software and thematically organized into six domains of functioning.ResultsFindings revealed some significant differences between twice-exceptional students and control groups consisting of gifted peers, students with clinically diagnosed challenges, and typically developing students. In addition, some case studies confirmed persistent traits either associated with giftedness or with challenges that appear to endure despite their coexistence.DiscussionThe findings suggest the need to adopt a personalized approach that account for the dynamic interplay between high potential and challenges, supporting more accurate identification and effective intervention.Systematic review registrationIdentifier: CRD42024549363 https://www.crd.york.ac.uk/PROSPERO/view/CRD42024549363.